PELATIHAN DAN PENYULUHAN PEMBUATAN BRIKET SAMPAH PLASTIK UNTUK KARANG TARUNA DI TPS 3R ”PONCO BANYAK” DI DESA MANTREN KARANGREJO MAGETAN - Rachman, Natriya Faisal; Zainul Arifin, Muhammad; Oktavia, Wahyuni; Kustanto, Jaka Septian; Surlitasari Dewi, Desi (Politeknik Perkeretaapian Indonesia Madiun, 2024)
Environmental problems due to the lack of effective waste management have become a serious challenge in this modern era, triggering air, land, and water pollution and damaging ecosystems. triggering air, soil, and water pollution and damaging ecosystems. Waste is piling up not only in urban areas but also in rural areas due to population growth, urbanization, and increasing consumption patterns. approach 3Rs (Reduce, Reuse, Recycle) approach has become urgent to reduce dependence on landfills and minimize the impact of landfills. on landfills and minimize negative environmental impacts. Village Mantren adopted this approach by establishing the 3R TPS